Integrated slope stability assessment in a complex geotechnical and hydrogeological setting - Campbell, R; Mackie, D; Anderson, WS (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Integration between geotechnical and hydrogeological groups for slope stability studies is often discussed but more rarely appropriately implemented. Although guidelines exist, experience has shown that the communication and technical integration between the geotechnical and hydrogeological teams can be problematic. This paper presents an example of a holistic integration process which builds on established best practice guidelines rather than attempting to re-invent the currently accepted methodology. The Galore Creek copper-gold project, located in northwestern British Columbia, has been chosen as an illustrative case study. The Galore Creek copper-gold deposit, owned by the Galore Creek Mining Corporation (GCMC), currently includes plans for three open pits and additional mining-related infrastructure. The proposed mining area is surrounded by high, rugged, and ice-capped mountains on three sides with the Galore Valley opening to the north. The area experiences high levels of precipitation (rainfall and snow), as well as a significant annual freshet period. Combined with challenging topographic and climactic conditions, pit wall stability will be influenced by a structurally complex, variable rock mass, and locally elevated and compartmentalised pore water pressures. From the project outset, it was determined that an integrated approach to slope design would be required to consider the prevailing physical and environmental factors at play in the Galore Valley. To achieve the slope design in a practical and timely manner, both consultant and client geotechnical and hydrogeological teams met regularly from the initial planning and investigation stage through to the final stability modelling of the proposed pit slopes. With targeted field investigations providing the framework to update rock mass, structure, and hydrogeological characterisation, a number of potentially unstable zones within the mining area were highlighted. Elevated pore water pressures, combined with a locally weak rock mass and significant slope heights (in excess of 1,000 metres), required constant interaction between the geotechnical and hydrogeological groups to ensure that appropriate inputs and material behaviour were represented within the numerical stability models. A number of pore water pressure scenarios were evaluated including average freshet and full dewatering system failure. These varied pore water pressure scenarios were assessed and exported as 2D sections for limit equilibrium and finite element slope stability modelling. With the project schedule in mind, the hydrogeological and geotechnical teams were required to constantly exchange ideas and information since slope geometry had to remain flexible due to the evolving pit designs. Regeneration of pore pressure grids, for input into numerical stability models was not practical due to time constraints during this period. Phreatic surfaces were used to reasonably approximate the hydrogeological conditions, providing an efficient, hydrogeologically-sound approach for use in the frequent slope stability modelling iterations. Once stable phreatic-based designs were achieved, the hydrogeological team then developed pore pressure grids for selected pit wall sections. In most cases, the applied pore pressure grids produced comparable stability behaviour when compared to the approximated phreatic surfaces. By approximating the phreatic surface for individual slope models, the time consuming requirement of re−modelling the hydrogeological condition for each design iteration was avoided. The benefits realised through increased modelling efficiency represents a significant lesson taken from the Galore Creek integration exercise. Additionally, having both teams working in parallel, communicating inputs and results, design opportunities were realised due to a better understanding of the groundwater flow system and sensitivity of slope stability. Taking this integrated approach also reduced project delays and budget overruns related to excessive iterations between programs and groups.